PERILAKU MAKAN DAN KEJADIAN OBESITAS ANAK DI SEKOLAH DASAR NEGERI FAVORIT KOTA KENDARI PROVINSI SULAWESI TENGGARA - , Supiati, Prof. Dr. dr DJauhar Ismail, Sp. Ak ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bacground: Obesity is a health problem in developed countries as well as developing countries like Indonesia. National prevalence of overweight children aged 6-14 years is 9.5% in male and 6.4% in female. In Sulawesi Tenggara 6,2% of male and 4.5% of female. Obesity, and in the of Kendari there was an increase of 0.15% in 2007 and 0, 26% in 2008. Obesity can be influenced by various factors. It issuspected that eating behavior is a major factor., so we want to know, how big is the eating behaviors contribute to childrenâs obesity Objective: To determine the relationship of eating behavior and incidence of childhood obesity in one favorite public elementary school in Kendari Sulawesi Tenggara Province Methods: This research was observational with cross sectional study design and was conducted in May 2010. This study tried to seethe relationship between the independent variables, eating behavior, to the dependent variable or obesity in children. Data was analysed using comparative test (chi square), and logistic regression Results: there was significant correlation between eating behavior and obese incidence (p<0.01) with the power of prevalence ration (PR) was protective in their nature (PR= 1/0.12 = 8.3 In other words, the subject with healthy eating behavior had probability 8.3 times greater to not obese Conclusion: There was significant correlation between diet behavior to the obesity in the children with the power of correlation and prevalence ratio was protective. The subject with healthy diet behavior had probability of 8.3 times to avoid obese incidence compared to the subject with non healthy eating behavior